Pelelangan Barang Gadai Dalam Persfektif Islam - Dewi Oktayani (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2019)
Pawn is an alternative for people who experience economic problems but do not want to lose their valuable possessions. The pawn can be done in the pawnshop as well as other financial institutions that provide pawn services. In Islam, the pawn is known as Ar-Rahn, which is to hold one of the borrower's assets from the loan he received. In a sharia pawnshop, the auction system applies to customers, if the customer is unable to pay his debt after maturity. The sale of liens after maturity is legal. That, according to the purpose of the understanding of the nature of the pawning itself, that is, as a trustee of a debt to be fulfilled. If the debtor is unable to pay the debt, the pawned goods can be sold to pay the debt, by representing the seller to a fair and trusted person. Auction according to sharia must also be able to be accounted for in Islamic law, which is free from the elements of gharar, maisir, usury and bathil.